The Influence Of Working Capital Turnover, Company Size And Debt To Equity Ratio On The Profitability Of Food And Beverage Subsector Companies Listed On Th - Khairunnisa, Khairunnisa; Nurismalatri, Nurismalatri (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
This study aims to analyze the effect of Working Capital Turnover, Firm Size, and Debt to Equity Ratio on Profitability in eight food and beverage sub-sector companies during the 2019-2023 period. Using a quantitative method with panel data regression and analysis conducted through Eviews12, this research applies Descriptive Statistical Analysis, Classical Assumption Tests, as well as T-Test and F-Test. The results indicate that, partially, Working Capital Turnover, Firm Size, and Debt to Equity Ratio do not have a significant effect on Profitability. However, simultaneously, these three variables influence Profitability, as shown by F-statistic 15.97120 > F-table 2.866. The coefficient of determination reveals that the research variables explain 84.63% of Profitability, while the remaining 15.37% is influenced by other factors not discussed in this study.